Optimizing Parameters of End Mill Cutting Tools for Milling Process - Amran, Muhammad Azamuddin; Mohd Amin, Azriszul (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The tool wear is one aspect that want to be avoided in machining processes especially milling. The cutting tools will get worn out when used in certain period. When the tool wear rate can be minimized, it can give advantages such as cost saving and better performance when milling. To achieve the goal, which is minimize tool wear, optimum milling parameter can be applied. So, the purpose of this thesis is to optimize tool wear by reduce it to the minimum level in milling process. The Taguchi technique may be used to determine which combination of parameter values works best. One popular strategy for designing experiments that is straightforward and systematic is the Taguchi method. To conduct the research, the Pinnacle conventional milling machine was applied on. The SZH10 Olympus optical microscope was used to assess the tool wear on the end mills. The collected data are then examined using Minitab's ANOVA statistical program and the Taguchi method. The goal of this investigation is to determine the ideal milling parameters that reduce end mill tool wear.